Tipologi tindak pidana Perbankan dalam perspektif Undang-Undang Nomor 10 Tahun 1998 tentang Perbankan - Purba, Indra Gunawan (Jurnal Normatif, 2024)
bank is an intermedial institution, namely a business entity that collects funds from the public in the form of savings and distributes them to the public in the form of credit and/or other forms in order to improve the standard of living of many people. The aim of collecting public funds and channeling them in the form of credit and other forms is to improve welfare, which is also part of the state's goals.Activities that can cause harm and threaten the failure to achieve banking objectives may be subject to criminal charges. Regulations regarding banking crimes are regulated in Law number 10 of 1998 concerning amendments to Law Number 7 of 1992 concerning banking. Several articles regarding acts that can be punished are regulated in this law.In order to make it easier to understand the actions that can be punished in the banking sector, this can be done by identifying the types of banking crimes. This article outlines the typology of banking criminal acts based on laws and regulations in Indonesia.